PENGARUH CITRA MEREK, HARGA, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN RAKET DI TOKO AGUS SPORT - Solehudin, Moh; Hendriati, Yossi (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
This research aims to find out the influence of brand image, price, and product quality on racket purchasing decisions at the Agus Sport store. In this research, a quantitative method was used in which data were obtained from survey results and questionnaire data processing based on statistical procedures. Based on Yount's formula, the sample in this study was 55 respondents. In this study, the results of the regression equation Y = -0,953+ 0.124X1 + 0.187X2 + 0.307X3 + e. Brand image variable has no effect on purchasing decisions with tcount (0.848) < ttable (2.00758), price variable has no effect on purchasing decisions with tcount (1.165) < ttable (2.00758), product quality variable has influence on purchasing decisions with tcount (4.025) > ttable (2.00758), and brand image, price, and product quality variables simultaneously influence by showing the results of calculations Fcount (29.334) > Ftable (2.79) where if Fcount > Ftable . While the R2 value is 0.633 or 63.3%, which indicates that the independent variables (X1, X2, X3) affect the dependent variable (Y) by 63.3%, while the remaining 36.7% is influenced by other variables outside this research.